Alpha-lipoic acid improves the quality of ram spermatozoa stored at 4°C by reducing oxidative stress and increasing mitochondrial potential - Sun, Xiaomei; Zhang, Liuming; Kang, Yan; Wang, Xuyang; Jiang, Caiyu; Wang, Jian; Sohail, Tariq; Li, Yongjun (Frontiers in Veterinary Science, 2024)
Ram spermatozoa inevitably produce a large number of reactive oxygen species (ROS) during liquid storage, leading to oxidative stress and a decline of spermatozoa quality. Therefore, it is particularly important to add exogenous antioxidants during the process of semen liquid preservation. The purpose of this study is to investigate whether adding alpha-lipoic acid (ALA) to ram semen can reduce oxidative stress and enhance spermatozoa quality during the liquid storage at 4 ℃. Different concentrations of ALA (0, 0.025, 0.05, 0.1, 0.5, 1 mM) were added to semen and stored at 4 ℃. During storage at 4 ℃, spermatozoa motility, kinetic pa-rameters, membrane integrity, acrosome integrity, energy metabolism parameters (mitochon-drial membrane potential (ΔΨM) and adenosine triphosphate (ATP)) and oxidative stress pa-rameters (ROS, malondialdehyde (MDA), total antioxidant capacity (TAC), superoxide dis-mutase (SOD)) were assessed. The results indicated that 0.1 mM ALA significantly (p＜0.05) improved spermatozoa total motility (TM) and progressive motility (PM), plasma membrane integrity, acrosome integrity, ΔΨM, ATP, TAC, and SOD, while significantly (p＜0.05) re-ducing spermatozoa ROS and MDA content compared to the control group. In conclusion, ALA can reduce damage caused by oxidative stress in spermatozoa and effectively improve the quality of semen preserved at 4 ℃. And the optimal concentration is 0.1 mM.